Identification of patient-specific CD4+ and CD8+ T cell neoantigens through HLA-unbiased genetic screens - Cattaneo, Chiara M.; Battaglia, Thomas; Urbanus, Jos; Moravec, Ziva; Voogd, Rhianne; de Groot, Rosa; Hartemink, Koen J.; Haanen, John B. A. G.; Voest, Emile E.; Schumacher, Ton N.; Scheper, Wouter (Nature biotechnology, 2023)
Cancer neoantigens that arise from tumor mutations are drivers of tumor-specific T cell responses, but identification of T cell-recognized neoantigens in individual patients is challenging. Previous methods have restricted antigen discovery to selected HLA alleles, thereby limiting the breadth of neoantigen repertoires that can be uncovered. Here, we develop a genetic neoantigen screening system that allows sensitive identification of CD4 + and CD8 + T cell-recognized neoantigens across patients’ complete HLA genotypes. Patient-specific tumor neoantigens are recognized by T cells.